Analisis tren fashion hijab modern di kalangan remaja dan implikasinya terhadap nilai syariat islam - Septiani, Ariani Candra Dwi (Maliki Interdisciplinary Journal, 2025)
In this modern era, the meaning of hijab which should be a form of identity and obedience for Muslim women has changed. Many of today’s teenagers tend to follow modern hijab fashion trends that prioritize fashion and style in appearance by ignoring the values of Islamic law, namely hijab to cover the aurat. This phenomenon is increasingly seen among teenagers who often combine hijab with fashionable clothing styles. In addition, social media also has a huge influence on the current hijab trend, for example hijab influencers or fashion bloggers who have indirectly created new standards of dress, which are sometimes not in accordance with Islamic law. As a result, teenagers today are less aware of the true meaning of hijab and are trapped in the mindset of wearing hijab just to fulfill their style. Therefore, understanding the Islamic Shari’ah about the recommendations for good Muslim dress according to the Shari’ah is important to help a Muslim, especially for women, in choosing or sorting out Muslim clothing that is in accordance with the Shari’ah.